2020
DOI: 10.1007/s00268-020-05461-x
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers to Effective Transfusion Practices in Limited‐Resource Settings: From Infrastructure to Cultural Beliefs

Abstract: Background Surgery and anesthesia are indivisible parts of health care, but safe and timely care requires more than operating rooms and skilled providers. One vital component of a functional surgical system is reliable blood transfusion. While almost half of all blood is donated in high-income countries (HICs), over eighty percent of the global population lives outside of these countries. High-income countries have on average 30 donations per 1000 people, and the average age of transfusion recipient is over 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Our study substantiated difficulties ensuring adequate blood products for patients at the hospital level 5 16 21 24. Respondents described that insufficient blood inventories contributed to delays in treatment for patients.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Our study substantiated difficulties ensuring adequate blood products for patients at the hospital level 5 16 21 24. Respondents described that insufficient blood inventories contributed to delays in treatment for patients.…”
Section: Discussionsupporting
confidence: 65%
“…Much of the published literature about blood transfusion in LMICs focuses on the safety of the blood supply and the risk of transfusion-transmitted diseases 2 4 9. While these topics are critically important, hospital-based transfusion practices and resources at the local level are essential determinants impacting patient care and outcomes 18 21 23. The HBTS provides a vital service to ensure enough blood for patients at the facility and that the blood is used safely and efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both developed and developing countries, inappropriate prescription of blood components occurs in up to 36% of cases 2 . The rational prescription of transfusion therapies is essential due to limited resources and growing demand 3 . Moreover, several studies have shown that aggressive correction of anemia, thrombocytopenia, and coagulopathies does not necessarily result in better clinical outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%